2018
DOI: 10.1002/bjs.10829
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of platysma muscle suture versus no suture for wound closure after thyroid surgery

Abstract: Background: Suturing the platysma muscle during wound closure after thyroid surgery is frequently described in the literature. There is no prospective evidence to support its use or benefit. The aim of this study was to evaluate how a platysma muscle suture influences initial postoperative pain following thyroid surgery.Methods: Patients were assigned randomly to receive a platysma suture or no platysma suture in this prospective, patient-blinded trial. The duration of follow-up was 6 months. The primary endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Nonetheless, the overall incidence of these complications was obtained as 14.5%, which was higher with 6% of post-thyroidectomy ulceration complications in another study (10). The average hospitalization length was 2 days in both groups, which was consistent with the findings of Senne et al studies, and there was no difference between the two groups (9).…”
Section: Discussionsupporting
confidence: 77%
“…Nonetheless, the overall incidence of these complications was obtained as 14.5%, which was higher with 6% of post-thyroidectomy ulceration complications in another study (10). The average hospitalization length was 2 days in both groups, which was consistent with the findings of Senne et al studies, and there was no difference between the two groups (9).…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, more and more research is now focused on preventing or at least diminishing the surgical pain whenever possible 12,14 . A recent study claimed that non-suturing of platysma was associated with significantly lesser pain in the post-operative period and recommend it in future practice 15 .…”
Section: Discussionmentioning
confidence: 99%
“…For all studies comparing closure method with staples, the authors reported closure of platysma and/or subcutaneous tissue before final epidermal layer closure with either staples, suture or glue. A recent study suggested that including platysma closure does not influence cosmetic results …”
Section: Discussionmentioning
confidence: 99%
“…For all studies comparing closure method with staples, the authors reported closure of platysma and/or subcutaneous tissue before final epidermal layer closure with either staples, suture or glue. A recent study suggested that including platysma closure does not influence cosmetic results 17. Postoperative haemorrhage formation occurs between 0.36% and 4.3% of cases, and a rapidly expanding haematoma can cause sudden airway compromise 18.…”
mentioning
confidence: 99%